Integrating research: the case of aging in a health research institute - Itziar Vergara; Ander Matheu; Julio Arrizabalaga (International Journal of Integrated Care, 2019)
Introduction: When integrated care is conceptualized and assessed, health research has to be included in the whole picture. Health research needs to be considered when defining health policies, when building health systems and when setting health professionals’ daily agenda. This is the only way of building a culture of research and of reassuring the impact of public financed research projects in population health outcomes. One of the structures chosen to facilitate the integration of research into health organizations are the Health Research Institutes. The aim of this kind of structure, promoted by Carlos III Health Institute, is to develop high quality basic, epidemiological and clinical research to be easily transferred to health systems, to patients and to society. Biodonostia Health Research Institute (Biodonostia HRS) was the first of its kind at the Basque Country to be recognized. Description of policy context and objective: Besides the development of the existing seven research areas at Biodonostia HRI, in 2013 a strategy for aging research was defined in order to facilitate the emergence of knew knowledge and the collaboration among already settled research groups. Every group was invited to participate and a number of already existing research lines related to aging were identified and new ones were proposed. The development of the new area was based solely on the interest of researchers of targeting aging within their area of expertise, the interest of collaborating with other groups and the decided support from the Institute. Some of the defined research lines were: biology of aging, neurodegeneration, oncogeriatry and frailty (biomarkers and management at primary care). Targeted population: The invitation to be a part of this new strategy was oriented to all the existing groups, but once those were involved, it got wider: the health system (OSI Donostialdea, OSI Bidasoa, Osakidetza general directorate, Health Department of the Basque Country Government), the social system (Diputación de Gipuzkoa and Matía Institute), Technology Centers (Tecnalia, Cidetec, among others) and the Economy Department of the Basque Country Government. Highlights and Comments on transferability: The main highlights have taken place a different levels: at the macro level, this transversal area has been framed in the Basque Country Smart Specialization Strategy and the European International Partnership of Active and Healthy Ageing (EIP AHA) and at CIBERFES, the national network of research on  frailty and aging. At a meso level, the results generated are being considered for the development of Osakidetza’s Strategic Plan, specifically the Program for the care of the elderly. And, finally, at the micro level, the activities developed have helped to involve a high number of health professionals in research related tasks. Conclusions: A Health Research Institute is able to define research strategies and policies that may act as triggers to enhance already existing activity and to make emerge new one, creating a network of collaboration and with capacity to impact health services provision and population health outcomes.